Lethal risks and New Zealand police / ngā pirihimana o aotearoa: contemporary analysis of lethal risks arising from subject-related interactions and interventions by law enforcement officers in a national police service - Shortt, Richard S. (Springer, 2024)
PART I The lethal risks context and how they are managed: Chapter 1 Introduction -- Chapter 2 Methodology -- Chapter 3 Risk Management and Lethal Risks – Organizational -- Chapter 4 Risk Management – Tactical -- PART II The nature of lethal risks between 1886 and 2019: Chapter 5 Environmental Variables: Population, Officer Numbers and Who Faces Lethal Risk? -- Chapter 6 Analysis: 1886 to 1999 (Publicly Available Reporting) -- Chapter 7 Analysis: 1886 to 1999 (Publicly Available Reporting) -- PART III Observations and thoughts regarding the research and the future: Chapter 8 Observations -- Chapter 9 Where To From Here? -- Chapter 10 Conclusion.